Edukasi Persiapan Persalinan Pada Ibu Hamil Trimester III di Puskesmas Kalumpang Mamuju - Thalib, Kiki Uniatri (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2022)
The third trimester of pregnancy starts at 28 weeks to 40 weeks of gestation. Pregnant women tend to look worried at this gestational age, perhaps feeling the discomfort experienced by pregnant women in the third trimester, this discomfort can affect labor and the postpartum period. In the second pillar of safe motherhood, it is stated that antenatal care is a means for pregnant women to prepare for the birthing process. Maternal unpreparedness for childbirth is one of the causes of the high maternal mortality rate. If during pregnancy there are obstetric complications and the mother does not know what preparations are needed before giving birth, then the mother will not receive appropriate and timely services. This activity aims to provide education regarding preparation for childbirth in the hope that pregnant women can know in advance the preparations for childbirth. In this activity, pre and posttests were carried out using a questionnaire to measure the knowledge of pregnant women and provide education using the counseling method. This activity was carried out at the Kalumpang Community Health Center. The results obtained from this activity were that the knowledge of pregnant women after counseling changed to good at 86.5% from previous knowledge which was adequate at 55.2%. This is because pregnant women receive additional information regarding preparation for childbirth through counseling. From this activity, it is hoped that all pregnant women will be active in using Maternal and Child Health books, not only keeping them but reading and studying them for maternal knowledge.